Population Characteristics and Diet of Sailfin Molly Poecilia velifera (Regan, 1914) (Poeciliidae; Cyprinodontiformes): an Alien Fish Invading Songkhla Lake Basin, Thailand - Suebpong Sa-nguansil (Prince of Songkla University, 2012)
Thesis ( M.Sc., Ecology)--Prince of Songkla University, 2010